Pendampingan Perancangan Balai Rukun Tetangga Untuk Memenuhi Fungsi Dasar Arsitektur Di Kawasan Hunian Masyarakat - Vijar Galax Putra Jagat Paryoko (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2020)
Rukun Tetangga (RT) hall generally is a facility that provides public space for formal and informal activities by communities in a residential area. Today, function of RT hall is not only being a public social facility, but also as a regional icon, which is an effort to self-actualization of local community. Thus, the purpose of designing a hall of RT 06 at Perumahan Dosen Untag Surabaya for the community is to overcome the issues, and for the accompanying education institution is to provide indirect education about the "building tasks” in architecture that are increasingly forgotten. The point is that although as a simple building, a RT hall must also fulfill its function as an architecture to accommodate activities, aesthetics, environmental filter, behavior modification, investment, and cultural symbols. This community service activity is carried out using consultation and assistance methods from the pre-design stage until planning document is produced. Evaluation of this activity shows that architectural design, although for a simple building, the socio-cultural issues of the community by considering the success of those six “building tasks” in architecture. The success of cultural symbols task in architectural imagery can be achieved with limited budget by choosing the right concept exploration method.